Pressure-tolerant survival mechanism of Schizophyllum commune 20R-7-F01 isolated from deep sediments 2 kilometers below the seafloor - Zhao, Mengshi; Li, Dongxu; Liu, Jie; Fang, Jiasong; Liu, Changhong (Frontiers in Marine Science, 2024)
In anaerobic high hydrostatic pressure (HHP) sedimentary environments below the seafloor, fungi are found to dominate the eukaryotic communities, playing crucial ecological roles. However, the specific mechanisms by which fungi adapt to anaerobic HHP environments remain unclear. In this study, we investigated Schizophyllum commune 20R-7-F01 isolated from coal-bearing sediments at a depth of 2 km below the seafloor. By assessing the cell viability, biomass, and cell wall thickness changes of strain 20-7-1 under different HHP conditions, we observed that, compared to 0.1 MPa, strain 20-7-1 exhibited slower growth rates and decreased cell viability at 15 MPa and 35 MPa, yet demonstrated significant pressure tolerance.Transcriptomic and metabolomic analyses revealed that this strain activated the carbohydrate metabolic process to simultaneously utilize ethanol and lactic acid fermentation pathway. Additionally, it activates the oxidoreductase activity and hydrolase activity pathways to detoxify intracellular reactive oxygen species (ROS).Activation of the metal ion binding pathway increases the proportion of unsaturated fatty acids in the cell membrane, while instigation of the integral component of membrane pathway maintains cell wall structural stability. Furthermore, activation of the DNA repair pathway repairs DNA damage, demonstrating its comprehensive adaptive mechanisms against the HHP stress. These research findings deepen our understanding of fungal survival strategies and adaptation mechanisms in extreme 2 environments, laying the groundwork for further exploration of their roles in cycling of carbon, nitrogen, sulfur, and other elements in the deep biosphere.